Courage And Sincerity In Catherine Hardwicke's Red Riding Hood Movie (2011): An Existentialist Approach - Karuniawati, Arini (2012)
This study is about courage and sincerity in Red Riding Hood movie (2011). This objective of the study is to apply the Existentialist approach to analyze the courage and sincerity in Red Riding Hood. The writer uses Sartre's major point of Existentialism to answer the problem of the study. The study is descriptive qualitative research which data are taken from script in Red Riding Hood. The technique of analyzing data is descriptive. The study comes to the following conclusion. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, casting, mise-en-scene, cinematography, sound, and editing are related to each other and form the unity. Second, based on the existentialist analysis, human has different existence. The existence is based on different being, choice, and act. Human has a freedom to choose and then responsible for the existence. The responsibility will appear an anxiety. Catherine Hardwicke wants to convey a moral message that human has to defend the existence and has to struggle the life.